The Relationship Between Lifestyle and Hypertension in Healthcare Workers - Esa Zahirah (Miracle Journal Get Press, 2025)
The aim of this study was to examine the relationship between lifestyle and the incidence of hypertension in health workers and provide evidence-based recommendations that can be used in efforts to prevent and manage hypertension among medical personnel. Methods. This cross-sectional study involved 200 health workers working in hospitals and health care centres, with samples selected using purposive sampling technique based on predetermined inclusion and exclusion criteria. Data were collected through a structured questionnaire covering aspects of lifestyle, such as diet, physical activity, smoking habits, alcohol consumption, stress levels, and sleep quality. The data were analysed statistically using the chi-square test and logistic regression. Results. The results showed that unhealthy diet was the main risk factor, with 70% of health workers with poor diet having hypertension. Smoking habit showed a very strong association with hypertension (p=0.000), with 80% of smokers identified as having this condition. A total of 85% of individuals who consumed alcohol had hypertension, and 80% had poor sleep quality, which was significantly associated with high workloads and unhealthy lifestyles. Conclusion. This study confirms that although health workers have a good understanding of the hypertension risk factors, excessive workloads, unhealthy lifestyle, and low sleep quality remain major obstacles in the prevention of the development and management of the disease.